2021
DOI: 10.21203/rs.3.rs-866273/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distribution and risk assessment of heavy metals in soil in a commonly used mining area

Abstract: This study investigated the spatial, vertical and fraction distribution, multivariate statistical analysis, as well as assessed pollution levels and health risks posed by heavy metals at the Wenshan mining area. There were 6 sampling points at the site, from which a total of 32 samples were collected. The eastern and south-eastern parts of the site were heavily polluted, while the western and north-western parts were less contaminated. As pollution was particularly severe in the topsoil, with the mean value of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…The results of the carcinogenic risk evaluation in this study indicated that the three heavy metals Cr, As, and Cd that were found in the soil in the four study areas all had different degrees of carcinogenic risk for adults and children through ingestion, and the order of risk was Cr > As > Cd. The carcinogenic risk for humans was greater for children than adults, which is consistent with the results of Xu et al (2021) and Wang et al (2021). Exposure to Cd through dermal contact for both adults and children resulted in a carcinogenic risk of Cd that was not significant in the four study areas, while As had some carcinogenic risk for adults or children in some of the study areas.…”
Section: Carcinogenic Risk Evaluationsupporting
confidence: 90%
“…The results of the carcinogenic risk evaluation in this study indicated that the three heavy metals Cr, As, and Cd that were found in the soil in the four study areas all had different degrees of carcinogenic risk for adults and children through ingestion, and the order of risk was Cr > As > Cd. The carcinogenic risk for humans was greater for children than adults, which is consistent with the results of Xu et al (2021) and Wang et al (2021). Exposure to Cd through dermal contact for both adults and children resulted in a carcinogenic risk of Cd that was not significant in the four study areas, while As had some carcinogenic risk for adults or children in some of the study areas.…”
Section: Carcinogenic Risk Evaluationsupporting
confidence: 90%
“…Resource utilization is the recovery of useful resources from POFTs while achieving resource recovery. Excessive emissions of P, Mg, and Ca resources can disrupt ecological balance and endanger human health. , The recycling of P, Mg, and Ca resources is of great significance to people’s health, environmental protection, resource conservation, and cost reduction. A large number of researchers have recovered P, Mg, and Ca resources by calcination-carbonation, calcination-leaching, nitric acid leaching, and ammonia recycling and realize the resource utilization of POFTs.…”
Section: Comprehensive Utilization Methods Of Poftsmentioning
confidence: 99%
“…Regarding leaching time, the Cd concentration was high at the initial leaching stage, decreasing progressively with extended leaching time and finally stabilizing. Xu [50] studied the migration law of heavy metals in filling and reclamation materials. The results revealed that Zn, Cu, and Pb concentrations were released longer when exposed to rainfall, while Cr and Cd were released more rapidly.…”
Section: The Characteristics and Factors Influencing CD Leaching In Soilmentioning
confidence: 99%